A history of architecture: Settings and rituals - Spiro Kostof (Oxford Univ. Press, 1985)
The book ranges from the first prehistoric environments on record to the most recent examples of architectural and urban design. A landmark work of impressive scope, the book is enhanced by 800 halftone illustrations and 150 drawings especially prepared by architect Richard Tobias. It includes not only the religious, governmental, and upper-class monuments around which architectural history has usually beeb written but also the diversity of ordinary domestic, rural, and urban buildings and landscapes that surround them. Moreover, the book evaluates Western achievement in the context of contemporary cultures elsewhere; discusses the high points of imperial Rome along with Buddhist stupas and Han palaces; compares medieval Florence with medieval Cairo; and introduces Inca and Aztec cities as the Spanish conquistadores would have seen them